Effect of thermal aging and experimental studies on enhancement of the performance of solar photovoltaic panels - Natesan, Kapilan; Sadashiva Prabhu, S.; Narayanasamy, Srikanth; Mazlan, Norkhairunnisa (Praise Worthy Prize S.r.l, 2024)
The urgent need to solve the problems with conventional energy sources related to sustainability, the economy, and the environment has driven the shift from fossil fuels to solar Photovoltaic (PV) systems. The thermal aging of PV panels has been observed as they are exposed to continuous heating and cooling cycles, which may deteriorate the quality of PV cells. The research aims to identify the chemical variation among exposed and non-exposed PV cells. Further, overheating solar PV panels during summer due to higher solar radiation or atmospheric temperature reduces power output. The authors proposed the simplest method of cooling the panel using a wet sponge. With a primary focus on optimizing the sponge thickness for improved performance, this work examines the impact of wet sponge thickness on the cooling efficiency of solar PV panels under varied solar radiations with considerations of overall power output, temperature control, and heat dissipation. This also finds the optimum thickness for the reduction of its surface temperature during summer for maximum power output. Additionally, modeling related to surface temperature and heat transfer across wet sponges is proposed.